Supramolecular Chemistry of Biomimetic Systems - Li, Junbai; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book investigates the latest developments in supramolecular assembly systems for mimicking biological structures and functions. Consisting of 14 chapters, it covers various assembly systems, such as polysaccharides, peptides, proteins, biopolymers, natural materials and various hybrid systems. Further, it focuses on different types of supramolecular systems with particular functions or structures that are relevant to living systems. A number of modern techniques used to study the supramolecular systems, such as total internal reflection fluorescence microscopy (TIRFM) and two-photon confocal microscopy, are also introduced in detail. Unlike conventional books on supramolecular assemblies, this book highlights the functions of the assembly systems, particularly their biological applications. As such, it offers a valuable resource for experienced researchers, as well as graduate students working in the field of supramolecular chemistry and biomimetic systems.
Part 1 Introduction to Supramolecular Chemistry and Biomimetic Systems.- Molecular Biomimetics and Molecular Assembly.- Advantages of Self-Assembled Supramolecular Polymers towards Biological applications.- Part 2  Biomimetic Membranes.- Nanoarchitectonics of Biomimetic Membranes.- Part 3  Biomolecules Based Molecular Assembly.- Polysaccharides Based Microcapsules -- Hemoglobin Based Molecular Assembly -- Photosystem II based Multilayers -- Peptide based Supramolecular Chemistry -- Functional Nanomaterials via Self-assembly Based Modification of Natural Cellulosic Substances.- Part 4 Molecular Assembly of Motor proteins and artificial Micro-/Nanomotors.- Directional Transportation of Assembled Molecular Linear Motors -- Reconstitution of Motor Protein ATPase -- Controlled Molecular Assembly towards Self-Propelled Micro-/Nanomotors.- Part 5 Hierarchical Dendrimer, Polyoxometalates Complexes and Inorganic-organic Hybrid Systems -- Functional Dendrimer-based Vectors for Gene Delivery Applications -- Polyoxometalates and Their Complexes toward Biological Application -- Inorganic-Organic Hybrid Materials Based on Nanopolyoxometalates.
Keywords: Nanotechnology; Biomaterials; Biomedical engineering; Surfaces (Technology).; Thin films; Nanotechnology; Biomaterials; Biomedical Engineering and Bioengineering; Surfaces, Interfaces and Thin Film